Cosmopolitanisms and the Jews - Gelbin, Cathy S.; Gilman, Sander L (Social history, popular culture, and politics in Germany, 2017)
Cosmopolitanisms and the Jews adds significantly to contemporary scholarship on cosmopolitanism by making the experience of Jews central to the discussion, as it traces the evolution of Jewish cosmopolitanism over the last two centuries. The book sets out from an exploration of the nature and cultural-political implications of the shifting perceptions of Jewish mobility and fluidity around 1800, when modern cosmopolitanist discourse arose. Through a series of case studies, the authors analyze the historical and discursive junctures that mark the central paradigm shifts in the Jewish self-image.